2021
DOI: 10.3390/buildings11100425
|View full text |Cite
|
Sign up to set email alerts
|

Damage Assessment of Reinforced Concrete Elements Due to Corrosion Effect Using Dynamic Parameters: A Review

Abstract: Corrosion of reinforcement is one of the main problems related to the durability of reinforced concrete structures. This can cause cracks and a separation of the protective layer, as well as reducing strength and structural stiffness, which can result in numerous human casualties. Visual inspection is a standard method of assessing the condition of reinforced concrete structures whose limitations, such as time, interpretability, accessibility, etc., may affect its effectiveness. Therefore, damage determination… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…The change in mode shapes was not discussed in the literature references, possibly because mostly uniform corrosion damage was induced, which is expected to have a minor effect on the mode shapes, or because of an insufficient amount of accelerometers. A change in modal damping ratio might also indicate corrosion, 24,48,50 even though some of the previous studies have found the modal damping ratio to be less reliable for damage quantification. 46,47,62 The tests in Section 'Experimental program' confirmed the latter statement, as no correlation was found between the CL and modal damping ratio.…”
Section: Comparison Between the Literature And Experimental Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The change in mode shapes was not discussed in the literature references, possibly because mostly uniform corrosion damage was induced, which is expected to have a minor effect on the mode shapes, or because of an insufficient amount of accelerometers. A change in modal damping ratio might also indicate corrosion, 24,48,50 even though some of the previous studies have found the modal damping ratio to be less reliable for damage quantification. 46,47,62 The tests in Section 'Experimental program' confirmed the latter statement, as no correlation was found between the CL and modal damping ratio.…”
Section: Comparison Between the Literature And Experimental Resultsmentioning
confidence: 99%
“…Although vibration-based assessment of corroding RC structures seems promising, only few studies have investigated the effect of reinforcement corrosion in concrete on the modal characteristics. An overview of studies focusing on corrosion in RC was given by Duvnjak et al, 24 which illustrates that most experimental studies are performed in laboratory conditions. Hence, the present study mainly discusses laboratory tests.…”
Section: Introductionmentioning
confidence: 99%
“…VBM is a more global technique which detects variations in structural stiffness based on modal characteristics [16,17]. Since corrosion causes a decrease in stiffness, VBM can be applied to detect corrosion damage in RC structures [18]. The corrosion damage is mainly portrayed by decreases in natural frequency [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…Among these, reinforcement corrosion is one of the most frequent causes, which seriously affects RC structures [1][2][3][4]. As shown in Figure 1, reinforcement corrosion seriously undermines the serviceability and structural performance of an RC structure [5]. Among major causes of reinforcement corrosion are chloride and carbonation, which result from atmospheric or environmental conditions, such as oceans, de-icing salts, and pollution.…”
Section: Introductionmentioning
confidence: 99%